Enhanced contribution of photovoltaic power systems to frequency control in future power systems - Julia Seidel; Florian Rauscher; Bernd Engel (IET Renewable Power Generation, 2021)
Abstract In contemporary grid infrastructure, grid frequency is still predominantly controlled by conventional power plants. However, the increasing installed power of distributed energy resources and the declining amount of synchronous generators will necessitate major participation of wind farms as well as photovoltaic systems in frequency control. From a technical point of view, PV inverters are able to provide not only manual but also automatic frequency restoration reserves as well as frequency containment reserves. However, market and regulatory conditions are not designed for them to participate yet. As power electronic‐based systems, photovoltaic inverters are able to react even faster to frequency deviations than conventional power plants. This characteristic is leveraged to analyse the contribution of photovoltaic systems to stabilise the grid frequency. Therefore, a new control reserve product, called fast frequency containment reserves is developed. It is shown that the frequency stability can be considerably improved by integrating PV systems into frequency control.